Pengaruh Capital Intensity dan Leverage terhadap Agresivitas Pajak Pada Sektor Property dan Real Estate di BEI Tahun 2021-2025 - Adistia Desiana Putri; Rahmat Mulyana Dali; Rasiman . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Taxes are the primary source of government revenue used to finance national development. However, efforts to optimize tax revenue continue to face challenges, one of which is tax aggressiveness practiced by companies to minimize their tax burden. The property and real estate sector is characterized by substantial fixed asset investments and relatively high debt utilization, which may influence corporate tax aggressiveness. This study aims to analyze the effect of capital intensity and leverage on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2025 period. This research employs a quantitative approach using secondary data obtained from the annual financial statements of property and real estate companies listed on the Indonesia Stock Exchange. The sample was selected through purposive sampling based on predetermined criteria. Data were collected using documentation techniques and analyzed using panel data regression with EViews 13 software. Tax aggressiveness, proxied by the Cash Effective Tax Rate (CETR), serves as the dependent variable, while capital intensity and leverage act as independent variables.The results indicate that capital intensity has a significant negative effect on tax aggressiveness, whereas leverage does not have a significant effect on tax aggressiveness. Simultaneously, capital intensity and leverage significantly affect tax aggressiveness in property and real estate companies. These findings suggest that fixed asset investment is a more dominant factor in influencing corporate tax policies than debt utilization. The results are expected to provide insights for company management, investors, and regulators in understanding the determinants of corporate tax aggressiveness.